A abertura do mercado de resseguro no Brasil : a inserção do IRB no novo cenário competitivo - Pinheiro, Joice (2008)
The opening of the reinsurance market is a mark in Brazilian insurance history. The publication of the Law 126/2007, on 15 January 2007, change the market operation to abolish the state monopoly of reinsurance. IRB, state reinsurer has monopolized the reinsurance market during 69 year, operating on the regulation, the execution and supervision of reinsurance politics, became a player in new market. This work aims to analyze reinsurance Brazilian industry, the possible scenarios from the opening reinsurance market. The Porter Model is used as reference to industry and competiros analyzis. Additionally, IRB case study is done using SWOT Model in conjunction with Critical Success Factor. The results from this work show that the new reinsurance market has the powerful potential for growth because the new reinsurance Law allowed the international reinsurer installation and the Brazilian reinsurer creation. IRB will to face a challenge according his state and monopolist origin. The SWOT analyse in conjunction with Critical Success Factor show some state reinsurer weaknesses wich can risk the organization future